Disability, anxiety and depression associated with medication-overuse headache can be considerably reduced by detoxification and prophylactic treatment. Results from a multicentre, multinational study (COMOESTAS project). (May 2014) - Bendtsen, L; Munksgaard, SB; Tassorelli, C; Nappi, G; Katsarava, Z; Lainez, M; Leston, JA; Fadic, R; Spadafora, S; Stoppini, A; Jensen, R; ,
Objective: The objective of this article is to investigate whether headache-related disability, depression and anxiety can be reduced by detoxification and prophylactic treatment in patients with medication-overuse headache (MOH). Methods: Patients with MOH were included from six centres in Europe and Latin America in a seven-month cohort study. Before and six months after treatment, the degree of disability was measured by the Migraine Disability Assessment (MIDAS) questionnaire, while anxiety and depression were measured by the Hospital Anxiety and Depression Scale (HADS). Results: A total of 694 patients with MOH were included, of whom 492 completed the study. Headache days were reduced by 58.4% from 23.6 to 9.8 days per month at six months ( p  < 0.001). The MIDAS score was reduced by 57.1% from baseline 59.9 to 25.7 ( p  < 0.001). Number of patients with depression was reduced by 50.7% from 195 to 96 and number of those with anxiety was reduced by 27.1% from 284 to 207 (both p  < 0.001). Conclusions: Disability, depression and anxiety were considerably reduced in patients with MOH by detoxification and prophylactic treatment. This emphasises the urgent need for increased awareness about avoiding overuse of headache medications and demonstrates that not only headache frequency but also disability are remarkably improved by adequate intervention.